Therapeutic potential of enzymes, neurosteroids, and synthetic steroids in neurodegenerative disorders: A critical review - Servi, Refik; Akkoc, Ramazan Fazil; Aksu, Feyza; Servi, Sueleyman (Pergamon-Elsevier Science Ltd, 2025)
Neurodegenerative disorders present a significant challenge to healthcare systems, mainly due to the limited availability of effective treatment options to halt or reverse disease progression. Endogenous steroids synthesized in the central nervous system, such as pregnenolone (PREG), dehydroepiandrosterone (DHEA), progesterone (PROG), and allopregnanolone (ALLO), have been identified as potential therapeutic agents for neurodegenerative diseases. Neurosteroids such as ALLO, DHEA, and PROG, as well as their synthetic analogs like Ganaxolene, Fluasterone, and Olexoxime, offer promising effects for conditions such as Alzheimer's disease (AD) and depression. Moreover, Brexanolone and Ganaxolone are synthetic steroids approved for the treatment of postpartum depression and epilepsy, respectively. Neurosteroids such as ALLO are crucial in modulating GABAergic neurotransmission and reducing neuroinflammation. These compounds enhance the activity of GABA-A receptors, leading to increased inhibitory signaling in the brain, which can help regulate mood, cognition, and neuroprotection. Small clinical trials and observational studies indicate that ALLO may have cognitive benefits, but no large-scale, definitive meta-analysis confirms a 20 % improvement in AD patients. Mitochondrial dysfunction plays a vital role in the pathogenesis of numerous neurological diseases due to the high-energy demand and sensitivity of neurons to oxidative stress. Reduced mitochondrial function leads to amyloid-beta plaques and tau tangles accumulation in AD. In Parkinson's disease (PD), mitochondrial dysfunction resulting from the PINK1 or Parkin genes leads to energy deficiencies and the accumulation of toxic byproducts. Mutations in genes such as SOD1, C9orf72, and TDP-43 have been associated with mitochondrial dysfunction in amyotrophic lateral sclerosis (ALS). Moreover, studies on these neurodegenerative diseases suggest that inflammation is not merely a consequence of neurodegeneration but is also an essential factor in this process. Many neurological disorders involve multifaceted interactions between genetics, the environment, and immune responses, making it difficult to pinpoint their exact causes. Future research aims to overcome these hurdles through genetic advances, regenerative medicine, and personalized therapies. Cutting-edge technologies such as artificial intelligence and high-throughput screening are expected to accelerate drug discovery and improve diagnostic accuracy. Increasing collaboration between interdisciplinary fields such as bioinformatics, neuroscience, and immunology will lead to innovative treatment strategies. This comprehensive review discusses the therapeutic effects of enzymes, neurosteroids, and synthetic steroids in different neurodegenerative diseases, particularly AD, PD, ALS, and MS. Potential challenges in the therapeutic use of neurosteroids, such as the limited bioavailability and off-target effects of synthetic steroids, are also discussed, and an up-to-date and comprehensive review of the impact of these steroids on neurodegenerative disorders is presented.
Keywords: Alzheimer's disease; Parkinson's disease; Mitochondrial dysfunction; GABAergic signaling; Anti-inflammatory effects; Allopregnanolone; Dehydroepiandrosterone; Synthetic steroids